MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS DENGAN MENGGUNAKAN INVITATION CARD PADA SISWA KELAS XI SMK TUNAS HARAPAN - Istiqomah, Istiqomah (Jurnal Analisis Pendidikan Sosial, 2024)
Mastery of English Vocabulary is a competency that must be possessed by grade XI Vocational High School. However, the reality in the field shows the level of mastery of English vocabulary in XI grade of SMK Tunas Harapan is still low. Based on these conditions, the purpose of this study is to improve English vocabulary by using invitation card . This research uses Classroom Action Research techniques. Classroom Action research procedures was conducted implementation, observation, and reflection. The implementation of the action is carried out in two cycles. The research subjects of grade XI TKJ 3 students of SMK Tunas Harapan semester 1that consis of 44 students. It’s data collection techniques are observations, interviews, and tests. The results showed the use invitation card can improve the mastery of English vocabulary of XI SMK.